A Case of Endobronchial Aspergilloma Associated with Foreign Body in Immunocompetent Patient without Underlying Lung Disease - Jung, Seung Won (The Korean Academy of Tuberculosis and Respiratory Diseases, 2013)
Aspergillus causes a variety of clinical syndromes in the lung including tracheobronchial aspergillosis, invasive aspergillosis, chronic necrotizing pulmonary aspergillosis, allergic bronchopulmonary aspergillosis, and aspergilloma. Aspergilloma usually results from ingrowths of colonized Aspergillus in damaged bronchial tree, pulmonary cyst or cavities of patients with underlying lung diseases. There are a few reports on endobronchial aspergilloma without underlying pulmonary lesion. We have experienced a case of endobronchial aspergilloma associated with foreign body developed in an immunocompetent patient without underlying lung diseases. A 59-year-old man is being hospitalized with recurring hemoptysis for 5 months. X-ray and computed tomography scans of chest showed a nodular opacity in superior segment of left lower lobe. Fiberoptic bronchoscopy revealed an irregular, mass-like, brownish material which totally obstructed the sub-segmental bronchus and a foreign body in superior segmental bronchus of the lower left lobe. Histopathologic examinations of biopsy specimen revealed fungal hyphae, characteristic of Aspergillus species.